LED airfield lighting system operation and maintenance - Burns, John E.; Dennie, Chuck; Elshetwy, Shady; Lean, Doron; Vigilante, Joe (Transportation Research Board, 2015)
This report provides guidance for operating and maintaining light-emitting diode (LED) airfield ground lighting systems, including taxi guidance signs, elevated light fixtures, and in-pavement light fixtures. The research team prepared its guidance based on a literature review, an extensive survey of nearly 50 airports, and case studies of 12 airports. The guidebook begins with an overview of regulatory requirements as they relate to LED airfield lighting and a summary of the survey and case studies. The report then provides guidance on maintenance, including acceptance testing and warranty, fixture obsolescence and spare part recommendations, preventive maintenance and refurbishment/repair, maintenance practices during pavement repair, and environmental factors (e.g., vibration and moisture). The guidebook also covers operational considerations, including circuit configuration, heaters, monitoring, photometric and chromaticity analysis, and return-on-investment. The guidebook is supplemented by sample system requirements and maintenance schedules. The guidebook will be of particular interest to airport operations and maintenance (O & M) practitioners seeking to maximize the potential O & M benefits that LED lighting offers as they integrate and/or replace older airfield lighting with this new technology.
At head of title: Airport Cooperative Research Program.
Keywords: Runways (Aeronautics) -- Lighting.; LED lighting.; Lighting.; Light emitting diodes.; elektronické knihy; electronic books